PENGARUH BUDAYA KERJA, PELATIHAN, DAN MOTIVASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PENGRAJIN BATIK DI SENTRA BATIK GIRILOYO YOGYAKARTA - Yosoa Satriadi Prihanto; Prayekti Prayekti (Jurnal Manajemen, 2018)
The purpose of this study was to analyze the influence work culture on OCB, influence training on OCB, influence motivation on OCB, and influence work culture, training, and motivation on OCB craftsman batik at Giriloyo, Yogyakarta. Data collection using a questionnaire, while data analysis techniques using multiple regression analysis by the F-test and T-test, and the classical assumption test of multicollinearity test, normality test, and heteroscedasticity.The results with level of significance 5% or 0,05 showed that work culture haven’t significant effect on OCB(0,460 > 0,05), training have significant effect on OCB(0.004 < 0,05), motivation have significant effect on OCB (0.038 < 0,05), and work culture, training, and motivation has significant effect on OCB craftsman batik at Giriloyo, Yogyakarta.